The Effect of Positive Affirmation Video on Bullying Behavior among Adolescents in a Junior High School in Cimahi, Indonesia - Rahmi Imelisa; Ibrahim Moch Bolla; Khrisna Wisnusakti; Andri Nurmansyah; Fifi Siti Fauziah Yani (Jurnal Keperawatan Muhammadiyah, 2026)
ABSTRACT Background: Bullying among adolescents remains a significant public health and mental health issue, particularly in school settings. Bullying behavior negatively affects adolescents’ psychological well-being, social functioning, and academic performance. Nurses play an important role in school-based mental health promotion through preventive and promotive interventions. One innovative approach that can be implemented is the use of positive affirmation delivered through audiovisual media. Objective: This study aimed to examine the effect of a positive affirmation video on bullying behavior among adolescents in a junior high school in Cimahi, Indonesia. Methods: This study employed a quantitative quasi-experimental design with a pretest–posttest without control group approach. The sample consisted of 60 junior high school students selected using purposive sampling. Bullying behavior was measured using the Indonesian version of the Illinois Bullying Scale (IBS), which has been tested for validity and reliability. The intervention consisted of a positive affirmation video delivered in three sessions, each lasting 10 minutes, within one week. Data were analyzed using descriptive statistics and the Wilcoxon signed-rank test. Results: The total bullying score before and after the intervention remained the same; however, significant changes were observed across subscales. There was a significant decrease in aggressive behavior and bystander behavior after the intervention (p < 0.001). The bully subscale did not show a statistically significant change (p = 0.193). An increase was observed in the victim subscale (p < 0.001), indicating improved awareness and recognition of bullying experiences among students. Conclusion: Positive affirmation video intervention effectively influenced specific dimensions of bullying behavior, particularly by reducing aggressive actions and passive bystander behavior while increasing students’ awareness of victimization. This intervention can be considered a practical and innovative nursing strategy in school-based mental health promotion to prevent and manage bullying among adolescents.